Chronic kidney disease: information on southern brazilian patients with kidney disease - 10.4025/actascihealthsci.v34ispec.16048 - Yamakawa, Roger Haruki; Saito, Patricia Keiko; Bedendo, João; Silva Junior, Waldir Veríssimo da; Carvalho, Maria Dalva de Barros; Borelli, Sueli Donizete (Acta Scientiarum. Health Sciences, 2012)
The profile of patients undergoing haemodialysis in the dialysis unit of Hospital Santa Casa de Maringá, Maringá PR Brazil, is provided. A questionnaire on social and economic data and underlying diseases prior to the Chronic Kidney Disease (CKD) identified the patients’ profile. The project was approved by the Ethics Committee of the institution. Eighty-three patients, with 54.21% males, were interviewed. Age bracket ranged between 20 and 59 years in 65.06% of patients. Only 27.71% maintained jobs after the diagnosis and the start of treatment; 63.86% had an average personal income between 1 and 3 minimum wages; 63.85% did not practice any physical activity. Moreover, 53.01% belonged to the European-Brazilian white group; 20.48% to the Afro-Brazilian brown group; 19.28% to the Afro-Brazilian Negro group; 6.02% to other ethnic groups. Further, 85.54% patients reported having an underlying disease prior to the CKD, namely, 61.45% were hypertensive; 31.33% were diabetics and 20.48% had other diseases. Results show the need of a greater attention to these patients’ health care to reduce the negative impacts related to the chronic disease focused.